Changes in the Diffusion Coefficient of Rhenium in a New Type of Nickel‐Based Single‐Crystal Superalloy during Homogenization. Issue 4 (19th December 2019) - Li, Yiling; Jia, Zhihong; Tang, Wei; Liang, Xiangfeng; Xu, Weitai; Zhao, Yutao
Abstract : Rhenium (Re) is the slowest‐diffusing element in nickel‐based single‐crystal (SC) superalloy, and its diffusion coefficient has deep influence on the research of homogenization. A model of diffusion of Re during homogenization is established in this work. Based on the model and the data in this experiment, the diffusion coefficient of Re ( D Re ) is 6.67 × 10 −3 μm 2 s −1 at 1300 °C, 7.99 × 10 −3 μm 2 s −1 at 1330 °C, and 1.86 × 10 −2 μm 2 s −1 at 1340 °C. The experimental data show that the D Re in SC structure is smaller than it in polycrystalline structure, which was measured by diffusion couple system. Also, the law of change of D Re during 1300–1340 °C does not conform the Arrhenius equation because of the undissolved γ′ phase. Abstract : Herein, a model of diffusion of rhenium (Re) during homogenization is established. The diffusion coefficient of Re between 1300 and 1340 °C (red line) is calculated by the model and compared with other conclusions (other lines). These differences are fully explained. Also, the change in the red line is explained by the phase transition.